Synergizing Digital Innovation, Sustainability, and Maqashid al-Shariah in the Global Islamic Economy - Azharsyah Ibrahim (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
This issue presents an extensive and timely collection of scholarly works that examine the continuing transformation of Islamic economics and finance in response to digital disruption, sustainability imperatives, institutional reform, and changing socio-economic behavior. The articles published in this volume engage with several critical domains, including the digitalization of Islamic social finance, the strengthening of zakat and waqf governance, the expansion of halal industries and halal tourism, the advancement of Islamic banking stability and corporate governance, and the evolving dynamics of Islamic capital markets and financial behavior. In addition, this edition places significant emphasis on the socio-economic application of Maqashid al-Shariah, particularly in the context of digital economic transformation, institutional efficiency, household resilience, and contemporary Islamic financial instruments. Collectively, these contributions offer rigorous theoretical reflections, robust empirical findings, and practical policy recommendations for building an Islamic economy that is ethical, inclusive, adaptive, sustainable, and spiritually grounded in the digital era.